Pharmacological Potential of the Endogenous Dipeptide Kyotorphin and Selected Derivatives - Perazzo, Juliana; Castanho, Miguel A. R. B.; Sá Santos, Sónia (Frontiers in Pharmacology, 2017)
The endogenous peptide kyotorphin (KTP) has been extensively studied since it was discovered in 1979. The dipeptide is distributed unevenly over the brain but the majority is concentrated in the cerebral cortex. The putative KTP receptor has not been identified yet. As many others neuropeptides, KTP clearance is mediated by extracellular peptidases and peptide transporters. From the wide spectrum of biological activity of KTP, analgesia was by far the most studied. The mechanism of action still unclear, but the researchers agree that KTP induces Met-enkephalins release. More recently, KTP was proposed as biomarker of Alzheimer disease (AD). Despite all that, KTP limited pharmacological value prompted the researchers to develop derivatives more lipophilic and therefore more prone to cross the blood-brain barrier (BBB), and also more resistant to enzymatic degradation. Conjugation of KTP with functional molecules, such as ibuprofen (Ib), generated a new class of compounds with additional biological properties. Moreover, the safety profile of these derivatives compared to opioids and their efficacy as neuroprotective agents greatly increases their pharmacological value.